THE IMPACT OF THE RUSSIAN EMPIRE’S CUSTOMS POLICY ON THE MARKETS OF TURKESTAN: A SOURCE REVIEW - Ernazarov Tuygun Rajabovich (Western European Studies, 2025)
This article analyzes the economic and political dimensions of the customs policy implemented by the Russian Empire in Central Asia, particularly in the Turkestan region, during the second half of the 19th century and the early 20th century. Based on historical sources, the study examines the Empire’s protectionist approach and its impact on local markets, international trade routes, and commercial relations with neighboring countries such as Iran, Afghanistan, and China. It also discusses the influence of customs policies on trade flows, local merchants’ activities, and the broader context of imperial interests
Keywords: Russian Empire; Turkestan; customs policy